Development and validation of a method to determine thiabendazole and o‐phenylphenol in wastewater using micellar liquid chromatography‐fluorescence detection. Issue 19 (13th April 2016) - Peris‐Vicente, Juan; Roca‐Genovés, Pasqual; Tayeb‐Cherif, Khaled; Esteve‐Romero, Josep
Abstract : A micellar liquid chromatographic method to determine thiabendazole (TBZ) and o‐phenylphenol in wastewater is described here. The sample was directly injected without any additional treatment other filtration. The pesticides were resolved in <11 min, using a mobile phase of 0.10 M SDS—6% 1‐pentanol buffered at pH 3 running through a C18 column at 1 mL/min. The detection was performed by fluorescence at 305/360 and 245/345 nm excitation/emission wavelengths for TBZ and o‐phenylphenol, respectively. The method was validated following the directives of the Validation and Peer Review of U.S. Environmental Protection Agency Chemical Methods of Analysis guidelines in terms of selectivity, quantitation range (0.01–0.02 to 2 mg/L), detection limit (0.005–0.008 mg/L), trueness (92.1–104.2%), precision (<13.9%), robustness (<6.6%), and stability under storage conditions. The procedure was applied to the screening of TBZ and o‐phenylphenol in wastewater samples from citrus packing plants, agricultural gutters, urban sewage, as well as in influent and effluent wastewater treatment plants.